2011
DOI: 10.1039/c1cc11179e
|View full text |Cite
|
Sign up to set email alerts
|

Highly plasmon-enhanced upconversion emissions from Au@β-NaYF4:Yb,Tm hybrid nanostructures

Abstract: Yb,Tm hybrid nanostructures. This demonstrates that the plasmon field enhancement effect is the main reason for the improved UC emission efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
123
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(129 citation statements)
references
References 22 publications
4
123
0
2
Order By: Relevance
“…The interplay between these two effects sets an upper limit on the maximum achievable efficiency improvement from a single particle. In a recent study, a 30 to 50-fold upconversion enhancement in the visible range was reported when a UCNP was covered with a 5-10 nm dielectric spacing layer before it was coated by metallic nanoparticles [22].…”
Section: Upconversion Enhancement Through Plasmonics Nanocavitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The interplay between these two effects sets an upper limit on the maximum achievable efficiency improvement from a single particle. In a recent study, a 30 to 50-fold upconversion enhancement in the visible range was reported when a UCNP was covered with a 5-10 nm dielectric spacing layer before it was coated by metallic nanoparticles [22].…”
Section: Upconversion Enhancement Through Plasmonics Nanocavitiesmentioning
confidence: 99%
“…So far, decorating individual UCNPs by gold nanoparticles has been perhaps one of the most promising approaches [21][22][23]. In this arrangement, the localization of the field due to the presence of metallic nanoparticles tends to enhance the radiative decay rates through the Purcell effect [36].…”
Section: Upconversion Enhancement Through Plasmonics Nanocavitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a series of similar upconversion nanocomposites with noble metals has been fabricated to enhance the upconversion emissions. [45][46][47][48][49] Unfortunately, most of this work focuses on observing the enhancement effects rather than describing the detailed mechanism behind them. Therefore, there is no confirmed information available to direct the design of such nanocomposites to further improve the upconversion emissions until now.…”
Section: Figurementioning
confidence: 99%
“…The recent trends in the field of lanthanide complexes are to introduce metal nanoparticles to tune its luminescent behavior and boost their efficiency for optical device applications. [11][12][13][14] Recently, Parola et al have given a detailed overview on different types of lanthanide based hybrid nanomaterials and demonstrated that, controlled coupling between plasmonics (attaching metal nanoparticles) and luminescence opens a wide field of intense research. 15 The luminescence mechanism of the lanthanide complexes are based on the ligand absorption coefficient and energy transfer to central metal ion (lanthanides).…”
Section: Introductionmentioning
confidence: 99%